МЕТОДОЛОГІЧНІ ЗАСАДИ ВИВЧЕННЯ СТАНУ СФОРМОВАНОСТІ КОМУНІКАТИВНОЇ КУЛЬТУРИ МАЙБУТНІХ УЧИТЕЛІВ (Педагогіка вищої та середньої школи, 2002)
In clause the advantages and lacks of various methods of testing of a state of communicative culture of the future teachers are opened.